Molecular profiling and genome‐wide analysis based on somatic copy number alterations in advanced colorectal cancers. Issue 3 (23rd December 2017) - Sugai, Tamotsu; Takahashi, Yayoi; Eizuka, Makoto; Sugimoto, Ryo; Fujita, Yasuko; Habano, Wataru; Otsuka, Kouki; Sasaki, Akira; Yamamoto, Eiichiro; Matsumoto, Takayuki; Suzuki, Hiromu
Abstract : To characterize somatic alterations in colorectal cancer (CRC), we conducted a genome‐scale analysis of 106 CRC specimens. We assessed comprehensive somatic copy number alterations (SCNAs) in these CRC specimens. In addition, we examined microsatellite instability (MSI; low and high), genetic mutations ( KRAS, BRAF, TP53, and PIK3CA ), and DNA methylation status (classified into low, intermediate, and high type). We stratified molecular alterations in the CRCs using a hierarchical cluster analysis. The examined CRCs could be categorized into three subgroups using hierarchical cluster analysis. Tumors in subgroup 1 were characterized by a low frequency of SCNAs and a high frequency of MSI‐high status, whereas tumors in subgroups 2 and 3 were closely associated with a high frequency of SCNAs. Tumors in subgroup 1 were preferentially present in the right‐sided colon and showed frequent MSI‐high status. Subgroup 3 was distinguished by specific alterations, including gains at 1q23‐44, 1p11‐36, 10q11‐26, 10p11‐13, 12q24‐24, and 13q33‐33. In contrast, tumors in subgroup 2 were characterized by copy‐neutral LOH at 12p12‐13, 1q24‐25, and 10q22. In addition, KRAS mutations were more frequently found in subgroup 3 than in subgroup 1. TP53 mutations and intermediate levels of DNA methylation were common alterations in the three subgroups. SCNAs contributed to sporadic CRC, and there were three subgroups based on SCNAs that played a different role in driving the development of this disease.